The Long Bone Histology of the Sauropodomorph, Antetonitrus ingenipes - Krupandan, Emil (2018)
This analysis of the long bone microstructure of Antetonitrus ingenipes fills a crucial gap in our understanding of the growth dynamics of sauropodomorph dinosaurs. The bone histology of basal Sauropodomorpha are often characterized by zonal tissue, and contrasts with that of more derived sauropod taxa which show a shift toward the deposition of uninterrupted fibrolamellar bone (with lines of growth being either absent or only present in the outer circumferential layer). In Antetonitrus, growth patterns in the youngest individuals exhibit uninterrupted fibrolamellar bone without any growth marks. Sub-adult individuals, also exhibit highly vascularized fibrolamellar bone throughout the cortex, as in more derived Sauropods and Mussaurus, but growth lines occur intermittently (although not regularly) throughout the cortex as in Lessemsaurus. This indicates that Antetonitrus does not exhibit the growth dynamics previously considered characteristic of Sauropoda. Despite this, the largest (and possibly the oldest femur, NMQR 1705/163) does show an incipient external fundamental system (EFS). Our findings further suggest that growth marks are decoupled from bone size, which indicates a level of developmental plasticity in this taxon. Modulations or textural shifts in the pattern of vascular channel arrangements throughout the fibrolamellar bone in the cortex may be related to periods of resource limitations, although the lack of consistency of these modulations suggest that it is unlikely due to seasonal fluctuations. Localized bands of radial fibrolamellar bone, followed by resumption of normal growth in two samples are interpreted as evidence of a disease infliction, and subsequent recovery thereof.